Transformasi Kurikulum Agama Islam Menuju Era Digital: Inovasi dan Literasi sebagai Fondasi Sukses - Rizky Maulana Aziz; Zainal Arifin; Mukh Nursikin (Tihamah: Jurnal Studi Islam, 2023)
This research delves into the role of innovation and literacy in the development of the Islamic Religious Education (PAI) curriculum that is relevant to the demands of the 21st century. By adopting a qualitative approach through a literature review, this study highlights the urgency of innovation in the curriculum as an essential element of modern education. The concept of innovation encompasses the use of technology, innovative teaching methods, and the development of a curriculum that aligns with the needs of the times. Particularly in the context of Islamic education, innovation has helped increase student motivation and a better understanding of their faith. Additionally, literacy, especially digital and media literacy, becomes a crucial foundation for the curriculum of the future. This enables students to navigate the increasingly interconnected world wisely, allowing them to critically evaluate and comprehend information. Overcoming the barriers to adopting innovation and literacy requires collaboration among teachers, students, and educational institutions. Recommendations for the future include curriculum updates that focus on innovation and the integration of literacy skills into all aspects of PAI learning, along with continuous teacher training. With a strong emphasis on innovation and literacy, Islamic religious education will be well-prepared to face the challenges of the future, preparing students to be competent and wise individuals in navigating the increasingly complex and interconnected world of the 21st century.